## Which of the following is not a quadratic equation (a) (y+1)square =6 (b) 2y square +5y=9 (c) (y+1)(y-1)=5 (d) y(y+1)(y+2)=6

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

## Answers ( )

Step-by-step explanation:The Elimination Method

Step 1: Multiply each equation by a suitable number so that the two equations have the same leading coefficient. …

Step 2: Subtract the second equation from the first.

Step 3: Solve this new equation for y.

Step 4: Substitute y = 2 into either Equation 1 or Equation 2 above and solve for x.